A Novel Combination of Fruits and Vegetables Prevents Diet-Induced Hepatic Steatosis and Metabolic Dysfunction in Mice. Issue 11 (16th September 2020) - Guo, Weimin; Wu, Dayong; Dao, Maria C; Li, Lijun; Lewis, Erin D; Ortega, Edwin F; Eom, Heesun; Thomas, Michael; Nikolova-Karakashian, Mariana; Meydani, Mohsen; Meydani, Simin N
ABSTRACT: Background: Epidemiological studies suggest that higher fruits and vegetables (F&V) consumption correlates with reduced risk of hepatic steatosis, yet evidence for causality and the underlying mechanisms is lacking. Objectives: We aimed to determine the causal relation between F&V consumption and improved metabolic disorders in mice fed high-fat (HF) (Experiment-1) or normal-fat (Experiment-2) diets and its underlying mechanisms. Methods: Six-week-old male C57BL/6J mice were randomly grouped and fed diets supplemented at 0%–15% (wt:wt) with a freeze-dried powder composed of 24 commonly consumed F&V (human equivalent of 0–9 servings/d) for 20 wk. In Experiment-1, mice were fed an HF (45% kcal fat) diet with 0% (HF0), 5%, 10%, or 15% (HF15) F&V or a matched low-fat control diet (10% kcal fat). In Experiment-2, mice were fed an AIN-93 diet (basal) (B, 16% kcal fat) with 0% (B0), 5%, 10%, or 15% (B15) F&V supplementation. Body weight and composition, food intake, hepatic steatosis, inflammation, ceramide levels, sphingomyelinase activity, and gut microbiota were assessed. Results: In Experiment-1, mice fed the HF15 diet had lower weight gain (17.9%), hepatic steatosis (48.4%), adipose tissue inflammation, blood (24.6%) and liver (33.9%) ceramide concentrations, and sphingomyelinase activity (38.8%) than HF0 mice ( P < 0.05 for all). In Experiment-2, mice fed the B15 diet had no significant changes in weight gain but showed less hepatic steatosis (28.5%), blood and adipose tissue inflammation, and lower blood (30.0%) ceramide concentrations than B0 mice ( P  < 0.05 for all). These F&V effects were associated with favorable microbiota changes. Conclusions: These findings represent the first evidence for a causal role of high F&V intake in mitigating hepatic steatosis in mice. These beneficial effects may be mediated through changes in ceramide and/or gut microbiota, and suggest that higher than currently recommended servings of F&V may be needed to achieve maximum health benefits.